Pelatihan Manajemen Rekam Medis dan Informasi Kesehatan di UPT Puskesmas Gumuruh - Desy Widyaningrum; Syaikhul Wahab; Nuke Dewi Utami Hamid; Ade Irma Suryani; Shinta Elvira; Santy Christinawati (PADMA, 2024)
Primary health care services require well-organized and accurate management of medical records and health information to support the quality of services and data-based decision-making. UPT Puskesmas Gumuruh, Bandung City, as one of the primary health care facilities, faces several challenges in managing medical records, including limited understanding of recording procedures, duplication of medical record numbers, and irregular document storage systems. These issues have affected the timeliness of reporting and the overall efficiency of health services. This community engagement program aimed to improve the knowledge and skills of medical record officers through training on medical record and health information management based on standard operational procedures in the medical record unit. The activity was implemented through a participatory approach, consisting of need assessment, material preparation, interactive training sessions, and evaluation of learning outcomes. The training materials covered document management, numbering and filing systems, record retention, and the application of confidentiality principles in health information. The results indicated an improvement in participants’ understanding and practical skills in managing medical record data in a structured and standardized manner. The training also fostered more professional and disciplined work behavior among participants in handling patient information. Overall, this activity contributed to improving service quality and strengthening health information management at UPT Puskesmas Gumuruh, Bandung City.